2018
DOI: 10.1038/s41598-018-26258-y
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cells as a Novel Source of Dental Tissue Cells

Abstract: While earlier studies have suggested that cells positive for hematopoietic markers can be found in dental tissues, it has yet to be confirmed. To conclusively demonstrate this, we utilized a unique transgenic model in which all hematopoietic cells are green fluorescent protein+ (GFP+). Pulp, periodontal ligament (PDL) and alveolar bone (AvB) cell culture analysis demonstrated numerous GFP+ cells, which were also CD45+ (indicating hematopoietic origin) and co-expressed markers of cellular populations in pulp (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition, MSCs are not the only source of osteogenic cells. Several previous studies reported other possible cell sources that could be converted to osteogenic cells, for example, endothelial cells [ 6 ], endoneurial progenitor cells [ 7 ], and hematopoietic stem cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MSCs are not the only source of osteogenic cells. Several previous studies reported other possible cell sources that could be converted to osteogenic cells, for example, endothelial cells [ 6 ], endoneurial progenitor cells [ 7 ], and hematopoietic stem cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that monocyte/macrophage progenitors differentiate into adipocytes [23]; however, most studies did not identify the type of hematopoietic cells that can differentiate directly into cells of other lineages. Mehrotra et al also reported that HSCs can differentiate into cells in pulp and 6-24% hematopoietic-derived cells were detected when cultured pulp cells were analyzed [10]. However, this indicates that a smaller number of hematopoietic-derived cells was present before culture and that the number of hematopoietic cells could also have been smaller.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using human teeth have shown that dental pulp contains few hematopoietic stem and progenitor cells (HSPCs) that supply immune cells [ 9 ]. However, it has also been reported that cells derived from hematopoietic stem cells (HSCs) are present in the dental pulp, periodontal ligament, and alveolar bone, and that hematopoietic cells differentiate into dental tissue cells [ 10 ]. This raises a new possibility for the existence of HSPCs in dental pulp.…”
Section: Introductionmentioning
confidence: 99%
“…These included 1) scleraxis, a transcription factor expressed in tendon progenitor populations and mature tendon and which has also been found in PDL fibroblasts (30)(31)(32)(33) and 2) neurofilament, a structural protein of mature nerve fibers, was seen in the pulp and also found in the PDL (34). The known pulp markers of progenitor cell populations, shown to be mesenchymal stem cells (MSC), alpha smooth muscle actin (aSMA) and CD44 (35)(36)(37)(38), were increased after drug treatment. Furthermore, the possibility of tissue de-differentiation followed by re-differentiation into mature tissue, a hallmark of classic epimorphic regeneration with .…”
Section: Introductionmentioning
confidence: 94%
“…Stem cell populations have been identified that are associated with teeth in the pulp chamber, at the base of growing roots, and in the PDL (59). Progenitor cell populations have been identified in periodontal tissue previously and express mesenchymal stem cell markers such as STRO-1, CD146, CD44, and αSMA (30)(31)(32)(33)(60)(61)(62).…”
Section: Induction Of Stem Cell Markersmentioning
confidence: 99%